Pengembangan Modul Pembelajaran Berbasis Masalah Menggunakan Nearpod untuk Meningkatkan Hasil Belajar Bahasa Indonesia di Sekolah Dasar - Rochati, Uci; Suriswo, Suriswo; Nugraha, Rahmad Agung (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to develop a teaching module based on Problem Based Learning (PBL) integrated with Nearpod technology for Indonesian language learning on the topic